The random walk of stock prices: implications of recent nonparametric tests - Christian M. Dahl; Steen Nielsen (Copenhagen Business School (CBS), Department of Economics, 2001)
This paper applies six recently developed nonparametric tests of serial independence to monthly US stock returns. Findings of previous studies based on the BDS test are sup-ported since most of the new tests also reject the random walk hypothesis. Furthermore, power properties of the new tests are compared with those of the BDS test. The latter has much power against ARCH and GARCH alternatives whereas some of the more recent tests are superior against other alternatives. Finally, the power study of this paper shows, contrary to common belief, that ARCH and GARCH effects do not seem to explain rejec-tion of the random walk.
hdl:10398/7650
Keywords: G12; 330; Random walk; nonparametric tests; stock returns